Tillage, Mulching and Nitrogen Fertilization Differentially Affects Soil Microbial Biomass, Microbial Populations and Bacterial Diversity in a Maize Cropping System - Nyamwange, Methuselah Mang'erere; Njeru, Ezekiel Mugendi; Mucheru-Muna, Monicah (Frontiers in Sustainable Food Systems, 2021)
Determination of biologically active components of the soil organic matter, such as soil microbial biomass carbon (C) and nitrogen (N) can be used as indicators for variations in soil productivity due to changes in soil management. Soil agronomic management practices bring about changes in the physical and chemical properties of the soil, resulting in variations in soil microbial biomass and microbial diversity. The effects of tillage, mulch and inorganic fertilizers on soil microbial biomass C and N, microbial populations and bacterial diversity were determined from the treatment combinations which had been applied for 5 years in Central Kenyan Highlands. The test crop used was maize (Zea mays L.). The study involved conventional and minimum tillage systems, mulching and inorganic fertilizers (120 kg N/ha). Tillage (P < 0.001), mulch (P < 0.001) and fertilizer (P = 0.009) significantly affected soil microbial biomass C and N whereby minimum tillage and mulch increased soil microbial biomass C and N. Interestingly, minimum tillage and mulch recorded the highest bacteria and fungi CFUs compared to conventional tillage and inorganic fertilizers. Only fertilizer and mulch (P < 0.001) had significant effect on actinobacteria CFUs. Amplified ribosomal DNA analysis (ARDRA) showed that the highest genetic distance of 0.611 was recorded between treatments conventional tillage + no mulch + no NPK fertilizer and conventional tillage + no mulch + NPK fertilizer. The results demonstrate a strong effect of soil management practices on microbial biomass C and N, microbial populations and bacteria diversity in agricultural soils.